Locating Diaspora: Afro-Caribbean Narratives of Migration and Settlement in Toronto, 1914–1929 - Toney, Jared (Urban History Review / Revue d'histoire urbaine, 2010)
This article examines the experiences of Afro-Caribbeans in Toronto in the early twentieth century. It identifies and analyzes the practices and processes of diaspora at the local level and considers ways in which discourses of community, nation, and race travelled between sites and across borders. In so doing, it investigates the ways in which immigrant identities were constituted, contested, and reformulated in the tension between local experience and diasporic consciousness. As well, it evaluates how borders shaped the contours of trans-local and transnational communities. By extrapolating from individual histories, this article identifies several key features, institutions, processes, and practices that defined the Afro-Caribbean experience in Toronto and informed local engagements with global black and West Indian diasporas. These factors include encounters with discrimination, employment patterns, social relations, and organizations like Marcus Garvey’s Universal Negro Improvement Association. By “locating diaspora” in Toronto, this article elucidates the intersection and ongoing dialectics between the local and the global, and illustrates the significance of borders in shaping migration networks and constituting diasporic communities.